Implementation of ARS-STR in STR for Effective Energy Transmission - Vetrichelvi, G.; Mohan Kumar, G. (Asian Journal of Electrical Sciences, 2013)
Wireless mesh networks (WMNs) have emerged as a key technology for next generation wireless networking. Because of their advantages over other wireless networks, WMNs are undergoing rapid progress and inspiring numerous applications. In multi-hop wireless mesh networks (WMNs) experience frequent link failures caused by channel interference, dynamic obstacles and/or applications bandwidth demands. These failures cause severe performance degradation in WMNs or require expensive, manual network management for their real-time recovery. This paper presents an Autonomous network Reconfiguration System (ARS-STR) that enables a multi-radio WMN to autonomously recover from local link failures to preserve network performance. ARS-STR also improves channel efficiency.